EXPERIENCES OF THE RUSSIAN FEDERATION IN ENHANCING FINANCIAL LITERACY SKILLS IN SCHOOLS - Shamansurova Zilola Abduvahitovna; Akhmadjonov Abdullokh (Web of Journals Publishing, 2024)
This article analyzes the financial literacy programs of the Russian Federation and explores ways to adapt them to the conditions of Uzbekistan. Emphasizing that financial literacy has a positive impact on economic stability and well-being of the population, the study notes the need for cooperation between the public and private sectors, the organization of special courses and training in educational institutions, as well as the use of modern technology. Suggestions and recommendations developed on the basis of the experience of the Russian Federation are of great importance in the formation of practical programs aimed at improving financial literacy in the school system of Uzbekistan.
Keywords: Education system of the Russian Federation, Ministry of Finance, primary education, financial games, financial literacy, financial literacy center, school education, economic sciences, financial knowledge.